342 CBT-I Has Sustained Effects on Insomnia Versus Heart-Failure Self-Management Education among Adults with Chronic Heart Failure. (3rd May 2021) - Redeker, Nancy; Bessette, Andrew; Breazeale, Stephen; Conley, Samantha; Hollenbeak, Christopher; Hwang, Youri; Iannacco, Joanne; Jacoby, Daniel; Kelly-Hauser, Jessica; Linsky, Sarah; Moemeka, Lesa; Nwanaji-Enwerem, Uzoji; et al.
Abstract: Introduction: Insomnia is common among adults with chronic heart failure (HF), often not explained by sleep apnea (SA), and associated with daytime symptoms and poor daytime function. The purpose of this randomized controlled trial was to evaluate the sustained effects of cognitive behavioral therapy for insomnia (CBT-I) on insomnia severity and sleep characteristics over 6 months among adults with stable chronic HF. Methods: We included adults with HF who had at least mild insomnia [Insomnia Severity Index (ISI) > 8] and no more than mild SA or SA treated with continuous positive airway pressure. We randomized in groups to 8 weeks of group CBT-I (Healthy Sleep: HS) [4 group sessions + calls on alternate weeks] or attention control (Healthy Hearts: HH) [HF self-management education + brief sleep hygiene] in the same format. We administered the ISI, the Pittsburgh Sleep Quality Index (PSQI), the Dysfunctional Beliefs & Attitudes about Sleep Scale (DBAS), and the Sleep Disturbance Questionnaire (SDQ) at baseline (T0), 2 weeks after treatment ended (T1) and at 6 months (T2). Statistical analysis included descriptive statistics and mixed effects models with random intercepts and slopes. Results: The sample include 175 participants (HS: N = 91; 62 + 13 years; 58% Male; 15% Black; 68% NY Heart Class II-III) (HH: N = 84; 64 + 12.5 years; 56% Male; 17% Black; 70% NY Heart Class II-III). There was no significant difference at baseline in demographic characteristics or the mean ISI [HS: 15.3 (4.5); HH: 14.4 (4.5)], but a greater percentage in the HS group had clinical/moderate-severe insomnia (ISI > 15) (HS: 60.4% vs. HH: 47%). The CBT-I intervention (HS) was associated with significant improvement in insomnia severity (ISI: p = .001), sleep quality (PSQI: p = .002), and sleep-related cognitions (DBAS: p = .0006; SDQ: p = .0138), and a modest effect on self-reported sleep duration (46 vs. 20 mins, p = .054), but no effect on sleep efficiency. At 6 months, 12.9% of the HS group, compared with 24.9% of the HH group had clinical insomnia. Conclusion: CBT-I has sustained effects on insomnia, sleep-quality, and sleep-related cognitions in people with HF. Support (if any): R01NR01691 (NSR, PI)